Assessing The Level Of Nomophobia Among Students - Fuady, Ikhsan; Prasanti, Ditha; Yusnita, Titien (MOTIVA: JURNAL PSIKOLOGI, 2024)
Nomophobia (phobia of disconnection from smartphones) has a serious impact on social and mental problems in society, so it is important to measure the high number of nomophobia as an effort to anticipate more serious societal problems. This study aims to determine the level of nomophobia among college students. This research method uses a survey approach conducted on 123 students in West Java. To find out the level of nomophobia among college students, descriptive statistical analysis was applied. The results of the analysis show that most students have a high dependence on smartphones, the level of nomophobia among students, most students are in the moderate and severe categories. The most severe dimension of nomophobia experienced by students is the fear of not being able to communicate and losing connectedness. These findings indicate that the current condition of students is quite apprehensive in terms of their dependence on smartphones. This dependence can have an impact on mental disorders as well as other social problems. Therefore, parents or policy makers need to make regulations or rules that limit smartphone dependency among students (or children in the context of parents)